Negotiating the pedagogical requirements of both explicit instruction and culturally responsive pedagogy in Far North Queensland: teaching explicitly, responding responsively - D'Aietti, Karen; Lewthwaite, Brian; Chigeza, Philemon (The Australian Journal of Indigenous Education, 2020)
Abstract This article documents a teaching journey in a 6/7 class with 20 Torres Strait Islander students in the curriculum area of literacy, over the course of one academic year. Specifically, this action research study explores a classroom teacher's efforts to navigate and respond to the prominent teaching model of explicit instruction and culturally responsive teaching, both of which inform policy statements in Far North Queensland. Using a reflective journal, teacher observations, informal student dialogue sessions, yarning circles and student work samples, the first author (D'Aietti) endeavoured to adjust her teaching practice to determine how best to meet her learners' needs. Through on-going critical reflection, engagement with two critical friends and in consultation with a cultural mentorship group, her teaching underwent transformation. One of the key findings of this study was that students want to learn, and for this to occur, teachers must independently navigate the curriculum documents, and in doing so, the explicit instruction model must be re-aligned, re-adjusted and re-positioned to suit Torres Strait Islander student needs.